Theory of correlated insulating behaviour and spin-triplet superconductivity in twisted double bilayer graphene - Jong Yeon Lee (Nature Portfolio, 2019)
Twisted bilayer graphene exhibits correlated electronic phases and superconductivity, but its precise nature is under debate. Here, Lee and Khalaf et al. study a twisted double bilayer graphene, where ferromagnetic insulator and spin triplet superconducting phases can be stabilized.